In Situ Metallic Coating of Atom Probe Specimen for Enhanced Yield, Performance, and Increased Field-of-View - Schwarz, Tim M; Woods, Eric; Singh, Mahander P; Chen, Xinren; Jung, Chanwon; Aota, Leonardo S; Jang, Kyuseon; Krämer, Mathias; Kim, Se-Ho; McCarroll, Ingrid; Gault, Baptiste (Microscopy and microanalysis, 2025)
Atom probe tomography requires needle-shaped specimens with a diameter typically below 100 nm, making them both very fragile and reactive, and defects (notches at grain boundaries or precipitates) are known to affect the yield and data quality. The use of a conformal coating directly on the sharpened specimen has been proposed to increase yield and reduce background. However, to date, these coatings have been applied ex situ and mostly are not uniform. Here, we report on the controlled focused-ion beam in situ deposition of a thin metal film on specimens immediately after specimen preparation. Different metallic targets e.g. Cr were attached to a micromanipulator via a conventional lift-out method and sputtered using Ga or Xe ions. We showcase the many advantages of coating specimens from metallic to nonmetallic materials. We have identified an increase in data quality and yield, an improvement of the mass resolution, as well as an increase in the effective field-of-view. This wider field-of-view enables visualization of the entire original specimen, allowing to detect the complete surface oxide layer around the specimen. The ease of implementation of the approach makes it very attractive for generalizing its use across a very wide range of atom probe analyses.